Porous lightweight composites reinforced with fibrous structures - Yang, Yiqi; Yu, Jianyong; Xu, Helan; Sun, Baozhong (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides a comprehensive coverage of raw materials, product design, processing technologies, performance properties, and current and prospective applications of diverse lightweight composites reinforced with fibrous structures. Contributed by internationally recognized experts in lightweight composites, for the first time, this book · focuses on composites reinforced with hollow organic fibers, such as feathers and straws, and inorganic fibers, such as hollow carbon fibers; · covers different technologies, such as 3D weaving, 3D braiding, and 3D knitting, for development of hollow fibrous structures as reinforcements; · provides an overview on technologies, such as foaming and supercritical drying, that induce pores or voids into matrices; · discusses specific applications of lightweight composites in areas such as biomedical engineering and automotive engineering.
Keywords: Materials science.; Textile industry.; Engineering.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books